IMPLEMENTATION OF CHARACTER EDUCATION AT SCHOOL - Nining Andriani; Suharli Suharli; Erma Suryani; Fatmawati Fatmawati (PROGRES PENDIDIKAN, 2023)
The purpose of this study was to determine the implementation of character education in schools. It is said that character education is not new, scientific studies on its effectiveness have only been applied sporadically for the last thirty-five years. Therefore, most of the application of character education is not motivated by a scientific basis. This article introduces a scientific perspective on character education and summarizes the basic research examining the student impact of school-based character education. This article uses the literature study method. Sources from previous articles related to the purpose of this study. There are 5 sources of journal articles that are used as literature reviews. Research results explaining the relationship between character education and academic achievement should include a greater representation of schools in the average and below-average achievement categories. In particular analysis, a study of the extent to which character education is implemented in schools that may have test scores under the spectrum, but never less than expected by their socio-economic characteristics, would be an important contribution to our understanding of the relationship between character education and academic achievement. Researchers recommend the need for more in-depth research on character education in early childhood education, before entering elementary school so that moral values are instilled from an early age. So that in the future character education will be presented starting from education at the PAUD level.